2020
DOI: 10.3390/ijerph17020578
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Health-Related Fitness Training Program on Motor Performance as Well as Hematological and Biochemical Parameters

Abstract: The study was aimed at designing a health exercise program appealing to inactive young men, and then testing the men’s metabolic responses to the program using common diagnostic markers of general health. Six men, aged 22–29 years, took a part in training program to increase their motor performance and improve general health conditions. Body composition parameters, clinical chemistry variables (metabolites, albumin, total protein, ferritin, C reactive protein, lipid profile, ions, and selected enzymes activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Scientific data (Hakman, Duditskaya, Slobozhaninov & Kovtun, 2020;Kostrzewa-Nowak, Nowakowska, Zwierko, Rybak, & Nowak, 2020) have confirmed that aqua fitness classes are the most effective for improving the physical state of adult women.…”
Section: Discussionmentioning
confidence: 89%
“…Scientific data (Hakman, Duditskaya, Slobozhaninov & Kovtun, 2020;Kostrzewa-Nowak, Nowakowska, Zwierko, Rybak, & Nowak, 2020) have confirmed that aqua fitness classes are the most effective for improving the physical state of adult women.…”
Section: Discussionmentioning
confidence: 89%
“…CK activity constitutes the most common enzymatic marker used in sport diagnostics, because physical effort can trigger rhabdomyolysis and the release of muscle cell content [ 6 , 9 , 30 ]. The common problem with this parameter is its huge variation in baseline values, with reference ranges for the general population dependent on age, sex, race, muscle mass, physical activity and climatic conditions [ 15 , 31 ]. Metabolic homeostasis is achieved approximately 48–72 h after physical effort [ 32 ] and for this reason CK activity is the most commonly used recovery marker.…”
Section: Discussionmentioning
confidence: 99%
“…Athletes’ capability to improve their training performance can also be reflected in their blood morphology [ 15 ]. It is known that VO 2 max correlates with O 2 transport capacity, aerobic capacity and total hemoglobin concentration in athletes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations